Engaging Technology: A Missing Link in the Sociological Study of Human Knowing and Acting - Prus, Robert; Mitchell, Richard G. (Qualitative Sociology Review, 2009)
Whereas technology has been the focus of much discourse in both public theatres and sociological arenas, comparatively little attention has been given to the study of the ways that people actually deal with technology as realms of human knowing and acting. Working from a symbolic interactionist perspective (Mead 1934; Blumer 1969) and drawing on classical Greek scholarship as well as some interim sources, this paper addresses technology as a humanly engaged process. Attending to human group life as "something in the making" and focusing on the activities entailed in encountering, using, developing, promoting, obtaining, and resisting instances of technology, this paper outlines a research agenda intended to foster situated (i.e. ethnographic) examinations of technologically-engaged, humanly enacted realities. It also serves as a reference point for assembling and comparing studies of the technology process that deal with this set of activities.